1999
DOI: 10.1086/314685
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Responses to Human Immunodeficiency Virus Type 1 (HIV‐1) gp120 Peptides in HIV‐1–Infected Individuals Immunized with HIV‐1 rgp120 or rgp160 Compared with Nonimmunized and Uninfected Controls

Abstract: The proliferative responses to a series of peptides constituting the human immunodeficiency virus type 1 (HIV-1) gp120 sequence were evaluated in 19 HIV-1-infected rgp160 vaccine recipients, 17 HIV-1-infected rgp120 vaccine recipients, 15 HIV-1-infected placebo recipients, and 18 HIV-1-uninfected controls. Many regions of the gp120 molecule were found to contribute proliferative epitopes, although there were clearly regions of relative dominance and silence. Vaccine recipients tended to have broader, more robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…26 Consistent with these findings, we also found that "core peptides" were also less likely to bind than the extended ICS peptides, which invariably contained the flanking regions.…”
Section: B Gamma Interferon Elispot Assay Results Bamako Malisupporting
confidence: 84%
“…26 Consistent with these findings, we also found that "core peptides" were also less likely to bind than the extended ICS peptides, which invariably contained the flanking regions.…”
Section: B Gamma Interferon Elispot Assay Results Bamako Malisupporting
confidence: 84%
“…Several groups have reported on the use of recombinant gp120 and gp160, the envelope protein of HIV. All studies have shown that the protein is well tolerated and safe, but the immune responses generated by these vaccines are generally not thought to be of a protective level (Sitz et al, 1999;McCormack et al, 2000;Cunningham et al, 2001). Protein vaccines drive the immune response towards the Th2 cellular response and generation of antibodies.…”
Section: Hiv-1 Vaccines In Developmentmentioning
confidence: 99%
“…Despite the presence of the strongest T‐cell epitope of gp120, which is active in vitro (3–7) and an exposed B‐cell epitope (8,9), the C‐terminus of the C2 region encompassing amino acids 280–306 is not immunogenic in humans (3,10–12). Absence of the active B‐cell epitope within this peptide indicates that antibodies in sera of HIV patients recognizing this region of HIV‐1 gp120 represent autoreactive antibodies elicited by some human antigen.…”
Section: Introductionmentioning
confidence: 99%